Non-Invasive Prenatal Diagnosis of Monogenic Disorders Through Bayesian- and Haplotype-Based Prediction of Fetal Genotype - Li, Jia; Lu, Jiaqi; Su, Fengxia; Yang, Jiexia; Ju, Jia; Lin, Yu; Xu, Jinjin; Qi, Yiming; Hou, Yaping; Wu, Jing; He, Wei; Yang, Zhengtao; et al. (Frontiers in Genetics, 2022)
Background: Non-invasive prenatal diagnosis (NIPD) can identify monogenic diseases early during pregnancy with negligible risk to fetus or mother, but the haplotyping methods involved sometimes cannot infer parental inheritance at heterozygous maternal or paternal loci or at loci for which haplotype or genome phasing data are missing. This study was performed to establish a method that can effectively recover the whole fetal genome using maternal plasma cell-free DNA (cfDNA) and parental genomic DNA sequencing data, and validate the method’s effectiveness in noninvasively detecting single nucleotide variations (SNVs), insertions and deletions (indels). Methods: A Bayesian model was developed to determine fetal genotypes using the plasma cfDNA and parental genomic DNA from five couples of healthy pregnancy. The Bayesian model was further integrated with a haplotype-based method to improve the inference accuracy of fetal genome and prediction outcomes of fetal genotypes. Five pregnancies with high risks of monogenic diseases were used to validate the effectiveness of this haplotype-assisted Bayesian approach for noninvasively detecting indels and pathogenic SNVs in fetus. Results: Analysis of healthy fetuses led to the following accuracies of prediction: maternal homozygous and paternal heterozygous loci, 96.2±5.8%; maternal heterozygous and paternal homozygous loci, 96.2±1.4%; and maternal heterozygous and paternal heterozygous loci, 87.2±4.7%. The respective accuracies of predicting insertions and deletions at these types of loci were 94.6±1.9%, 80.2±4.3%, and 79.3±3.3%. This approach detected pathogenic single-nucleotide variants and deletions with an accuracy of 87.5% in five fetuses with monogenic diseases. Conclusions: This approach was more accurate than methods based only on Bayesian inference. Our method may pave the way to accurate and reliable NIPD.